AKULTURASI BUDAYA ACEH DAN ARAB DALAM KEUNDURI MULOD (Forum Ilmu Sosial, 2012)
Maulid (the celebration of the birth of the Prophet Muhammad) has been form of acculturation of tradition (custom) in Aceh. At the level of culture and structure, it is called a complex trait. Traditions applied follow the tradition set in Arab countries. Maulid feast is a is unique customs and culture of Aceh. Of course, it is very relevant the lives of people in this area who has self-proclaimed to implement of Islamic law in everyday’s life. Basing the system by syariah, all aspects of life should be directed to the moral values of Islam. Attitudes, behaviors, manners should be based on Islamic law.